2009
DOI: 10.1590/s0034-71672009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnósticos de enfermagem em portadores da Síndrome da Imunodeficiência Adquirida

Abstract: RESUMO RESUMO RESUMO RESUMO RESUMOOs objetivos deste estudo foram identificar os diagnósticos de enfermagem mais freqüentes segundo a taxonomia II da NANDA em pacientes adultos portadores de HIV/aids e verificar com que freqüência as características definidoras, os fatores relacionados e de risco deram suporte para a elaboração destes. O levantamento dos dados foi realizado pelos pesquisadores nos 60 pacientes internados com HIV/aids e depois feita a verificação se os requisitos propostos pela NANDA para reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0
14

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 2 publications
4
28
0
14
Order By: Relevance
“…The nursing diagnosis "Risk for Infection", identified in 100% of the patients was found in this same frequency in another study carried out with patients with HIV/ AIDS in an admission Infectious and Parasitic Diseases Unit, in a public hospital in the city of São Paulo (18) , demonstrated by the following risk factors: invasive procedures, inadequate secondary defenses and immunosuppression (100%). The diagnosis was identified also in 100% of the patients admitted in the Gynecologic Oncology Ward (17) , and among the most frequent diagnosis in the study developed in Iceland (16) .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The nursing diagnosis "Risk for Infection", identified in 100% of the patients was found in this same frequency in another study carried out with patients with HIV/ AIDS in an admission Infectious and Parasitic Diseases Unit, in a public hospital in the city of São Paulo (18) , demonstrated by the following risk factors: invasive procedures, inadequate secondary defenses and immunosuppression (100%). The diagnosis was identified also in 100% of the patients admitted in the Gynecologic Oncology Ward (17) , and among the most frequent diagnosis in the study developed in Iceland (16) .…”
Section: Discussionmentioning
confidence: 70%
“…In the study with HIV/AIDS patients (18) , the diagnosis "Ineffective Protection" was identified in 100% of the patients, and the defining characteristics were: deficient immunity in 100%, dyspnea in 53.3%, disorientation in 45% and weakness and agitation in 31.6%, and the related factors were: altered blood profile, and immunological disorder (100%) and imbalanced nutrition (60%). This last finding draws attention because in the present study, 30% of the patients had medical diagnoses of HIV/AIDS or associated opportunistic diseases; whose main characteristic is immunological deficiency, however, the diagnosis "Ineffective Protection" was not made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies conducted with patients living with AIDS, this Nursing Diagnosis had a prevalence of 98% to 100%. (9,11) Leukopenia, thrombocytopenia, and anemia were related to immunodeficiency, which have its cause in viral replication and in the HIV mechanism of action, since it binds to the cell surface and destroys T CD4 lymphocytes, increasing susceptibility to opportunistic infections. (12) It is noteworthy that the presentation of fatigue in these patients is probably a result of these cellular changes, particularly the decrease in red blood cells, which contributes to the condition of anemia and dyspnea and weakness symptoms felt by the individual.…”
Section: Discussionmentioning
confidence: 99%